82nd ARFTG Microwave Measurement Conference 2013
DOI: 10.1109/arftg-2.2013.6737350
|View full text |Cite
|
Sign up to set email alerts
|

Investigating connection repeatability of waveguide devices at frequencies from 750 GHz to 1.1 THz

Abstract: This paper describes some investigations into the repeatability of connection of some waveguide devices in the WM-250 (WR-01) waveguide size over the recommended operational bandwidth 750 GHz to 1100 GHz. Three devices are investigated -a flush short-circuit, an offset short-circuit, and a near-matched load. These devices can be used as calibration standards for network analyzers, and so can be found in network analyzer calibration kits. The repeatability of the measured reflection coefficient is assessed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 2 publications
(3 reference statements)
0
13
0
Order By: Relevance
“…Poor repeatability introduces a significant component of random error in the measurement. Recent studies have shown that this can be a dominant source of error in the measurement [31][32][33].…”
Section: Calibrationmentioning
confidence: 99%
“…Poor repeatability introduces a significant component of random error in the measurement. Recent studies have shown that this can be a dominant source of error in the measurement [31][32][33].…”
Section: Calibrationmentioning
confidence: 99%
“…It is for this reason that it is not generally feasible to provide a complete uncertainty budget for a particular DUT before it has been measured by the system. Some work on assessing DUT repeatability in this waveguide size has been undertaken recently [39][40][41] for some selected one-port devices. These were high-reflecting devices (a flush short-circuit and an offset short-circuit) and a lowreflecting device (a near-matched load).…”
Section: Random Errorsmentioning
confidence: 99%
“…These were high-reflecting devices (a flush short-circuit and an offset short-circuit) and a lowreflecting device (a near-matched load). It was found in [39] that experimental standard deviations, calculated from a series of 12 repeat measurements made under essentially the same condition of measurement, varied from approximately 0.01 to 0.1 (in terms of linear reflection coefficient). This is equivalent to a standard uncertainty of the order of 0.029 [24].…”
Section: Random Errorsmentioning
confidence: 99%
“…Two recent papers [1,2] have presented investigations into the connection repeatability of some waveguide devices operating from 750 GHz to 1.1 THz (i.e. in the WM-250 waveguide size [3]).…”
Section: Introductionmentioning
confidence: 99%
“…This work used the same VNA test port and devices under test (DUTs) that were used for the previous investigations [1,2]. This enabled comparisons of connection repeatability performance to be made directly with these earlier investigations.…”
Section: Introductionmentioning
confidence: 99%